Prevention of sudden cardiac death in patients with Tetralogy of Fallot: Risk assessment and long term outcome. (15th October 2018) - Probst, Julia; Diller, Gerhard-Paul; Reinecke, Holger; Leitz, Patrick; Frommeyer, Gerrit; Orwat, Stefan; Vormbrock, Julia; Radke, Robert; de Torres Alba, Fernando; Kaleschke, Gerrit; Baumgartner, Helmut; Eckardt, Lars; et al.
Abstract: Background: In patients with repaired Tetralogy of Fallot (ToF), implantable cardioverter defibrillators (ICD) are considered reasonable in selected adults with multiple risk factors for sudden cardiac death. Patients and methods: We performed a retrospective cohort study of all 174 patients with repaired ToF who are followed at the University Hospital of Muenster. We analyzed data according to the risk score previously proposed by Khairy and coworkers and patient outcome. We analyzed data separately for patients without previous sustained ventricular tachycardia (VT) (risk stratification group, n = 157) and patients with VT/secondary prevention ICD (n = 17). Results: In the risk stratification group, a mean of 4 ± 1 risk score parameters were available. All six risk parameters were known in 10%, five in 14%. Risk score increased with availability of parameters. 15 patients with secondary prevention ICD had a mean risk score of 6.3 ± 2.2 (range 2–10). 11 patients of the risk stratification group with primary prevention ICD had a mean risk score 5.8 ± 2.4 (range 3–8). During follow-up of up to 14 years, five patients died (3%): at age 58, two at 69 and two at 76 years. Conclusion: In the majority of patients risk score variables were incomplete, severely limiting its applicability because the true score cannot be calculated. Risk scores were not different between patients with secondary prevention ICD and patients with ICD for primary prevention based on current guidelines. Standardization of follow-up and prospective evaluation of these standards in large prospective patient cohorts is desirable to improve risk stratification in patients with ToF. Highlights: Risk score increases with known risk factors, but follow-up is not standardized. Invasive tests are seldom indicated, preventing complete risk score calculation. Risk score was similar in patients with primary and secondary prevention ICD. Long-term outcome was favorable in the majority of patients. Proposal of a follow-up protocol